PENDIDIKAN AGAMA HINDU DALAM MEMBENTUK KARAKTER PESERTA DIDIK - Ni Wayan Sri Yustikia (Universitas Panji Sakti, 2022)
AbstractCharacter is a fundamental value that must be instilled in the formation of the personality of students. Good character will have a positive impact on the progress of the quality of students in order to achieve goals. Law Number 20 of 2013 concerning the National Education System Article 3 which requires character building from an early age. Hindu Religious Education is a sub-system of national education. In addition to encouraging spiritual intelligence, Hindu Religious Education also has efforts to produce intelligent students both intellectually and emotionally. In its implementation, Hindu religious education is inseparable from Tattwa, Morals, and Events which are often referred to as the Three Basic Frameworks of Hindu Religion. If students can understand and live up to it, let alone be able to apply it, then it is certain that the personality of students in carrying out their lives both at school and outside of school will prioritize positive things based on religious education. In Hinduism there are very many teachings that can be used as guidelines to shape the character of students including Tri Kaya Parisudha, Catur Marga, Catur Vidya and Catur Asrama. Therefore, more efforts must be made to apply the teachings contained in Hinduism in schools in order to form a young generation of quality and noble character.Keywords: Character, Hindu Religious Education